2000
DOI: 10.1161/01.hyp.35.2.574
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Central Systolic Pressure Augmentation

Abstract: Abstract-Less than 50% of the variance in left ventricular mass is explained by conventional factors such as age, blood pressure, and body size. Genetic influences may account for part of the unexplained variance. The central (aortic) pressure augmentation index has been suggested as a noninvasive measure of pulsatile load, which is a likely determinant of left ventricular mass. We quantified the genetic influence on augmentation index and determined the extent to which this influence is dependent on the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 55 publications
6
84
0
3
Order By: Relevance
“…Several studies have demonstrated that BP is partly determined genetically (9,25). Our present results are concordant with those of earlier studies, where the proportion of variance in BP accounted for by interindividual genetic differences ranges from 15 to 73% (8,9,14,15,16,20,24,37,39,42).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that BP is partly determined genetically (9,25). Our present results are concordant with those of earlier studies, where the proportion of variance in BP accounted for by interindividual genetic differences ranges from 15 to 73% (8,9,14,15,16,20,24,37,39,42).…”
Section: Discussionsupporting
confidence: 93%
“…These findings support the hypothesis that arterial stiffening may pathogenetically contribute to the development of hypertension in carriers of the T-allele. This study also supports the idea that stiffening of large arteries may be influenced by genetic factors, 24 and is not just a mere consequence of aging or the presence of cardiovascular disease. Similar to other genes of the cardiovascular system including endothelin gene variants, 25 an influence of the C825T polymorphism may first be detected in arterial parameters.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study, AIx was found to be higher in the offspring of families with hypertension than in control subjects after correction for known cardiovascular risk factors. 14 Because aortic PWV was similar in the 2 groups, this study 15 indicated the existence of a functional and/or structural decrease in the caliber of small arteries. The Strong Heart Study, 8 performed in 950 adult men and women from 13 American Indian communities, assessed the heritability of carotid stiffness, estimated as the proportion of residual phenotypic variance caused by the additive effects of genes after accounting for the effects of covariates (sex, age, diabetes, etc).…”
Section: Heritability Of Arterial Stiffnessmentioning
confidence: 69%
“…AIx inheritance has also been studied in twins, using a co-twin case-control analysis in monozygotic and dizygotic female twins. 15 A quantitative genetic modeling technique was used, based on comparison of the variancecovariance matrices for monozygotic and dizygotic twins. Up to 37% of the variance of AIx was found to be determined by genetic factors, and only a small proportion of the total variance was caused by genes also affecting height, heart rate, and mean BP.…”
Section: Heritability Of Arterial Stiffnessmentioning
confidence: 99%